THE EXAMINATION OF TOTAL HARDNESS ON DRINKING WATER WITH BOILING AND FILTER PROCESS USING COMPLEXOMETRY METHOD - AGUSTINA WILHELMINA DJUMA; FRENGKI OLLA (JURNAL INFO KESEHATAN, 2016)
Water with good quality is water which requires good conditions of physic, chemical, bacteriology, and radioactive. One of chemical requirement is total hardness (CaCO3) with maximum degree 500 mg/L. Water with high level hardness can cause several problems. One of these is harm for health (causing kidney infection). A way to decrease this level of hardness through heat and filter process. The aim of this research is to find out the value of total hardness of drinking water and to discover the decrease of its effectiveness after heat, stagnation, and filter process. Kind of research used is appearance experiment through five times replication. Method for examining total hardness is complexometry. Data are analyzed methodically using One Way ANOVA parametric examination. Samples consist of sample A (drinking water before being boiled/controlled), B (boiled, filtered hot once), C (boiled, filtered hot twice), D (boiled, filtered cold once), and E (boiled, filtered cold twice). After the examination, the result of value of total hardness value for sample A is 362,69 mg/L; B 161,32 mg/L; C 157, 43 mg/L; D 88, 30 mg/L and E 84,02 mg/L. The result of Anova examination shows value p < 0,05. Then, Post Hoc and Homogeneous Subsets examination which is performed reveals that sample D and E become the most effective in decreasing the value of total hardness. It is concluded that the value decrease occurred on drinking water after process of heat, stagnation, and filter. The effectiveness of decreasing total hardness has been gained on drinking water sample that run through boiling process, stagnation for two hours, and filter once (sample D) amount to 76%. All samples have fulfilled the requirements of total hardness value concerning to Health Minister Regulation (Permenkes) No. 492/Menkes/Per/IV/2010.